Psychotic Process in the COVID-19 Pandemic: Dopamine Effect - Ayşegül Dönmez; Gülseren Keskin (Psikiyatride Güncel Yaklaşımlar, 2024)
The global impact of severe acute respiratory syndrome COVID-19 has extended beyond physical health, significantly affecting mental well-being worldwide. Amid the pandemic's initial wave, COVID-19 patients exhibited symptoms of post-traumatic stress disorder and notably depressive symptoms. Alongside manifestations like delirium, confusion, agitation, and altered consciousness, prevalent mental health issues during the pandemic encompassed depression, anxiety, and insomnia. Individuals recovering from COVID-19 may face enduring psychiatric challenges post-hospital discharge, potentially linked to dopamine. Dopaminergic receptors might heighten the susceptibility of certain viruses to bind with the central nervous system, instigating viral encephalitis in the virus's early infection stages. Dopamine could also disrupt the human basal carotid body's respiratory response to hypoxia. Additionally, the virus could manipulate the immune system by elevating dopamine levels, facilitating viral entry. These findings emphasize the significance of considering dopamine's role in the diagnosis, treatment, and care of COVID-19 patients and those with diagnosed psychosis. Tailored interventions are crucial for individuals exhibiting distinctive features. Another intriguing aspect worthy of investigation is whether dopamine confers protection against COVID-19. This review article aims to elucidate the intricate relationship between the impactful COVID-19 pandemic and dopamine, shedding light on its potential implications and avenues for further exploration.